EFEKTIVITAS EFEKTIVITAS PENGGUNAAN LKPD BERBASIS PROBLEM BASED LEARNING TERHADAP SELF REGULATED LEARNING PESERTA DIDIK KELAS V SEKOLAH DASAR : EFEKTIVITAS PENGGUNAAN LKPD BERBASIS PROBLEM BASED LEARNING TERHADAP SELF REGULATED LEARNING PESERTA DIDIK KELAS V SEKOLAH DASAR - Rohmah Shela Saputri; Amrina Izzatika; Nindy Profithasari; Fadhillah Khairani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
The problem in this study was that elementary school students’ self-regulated learning (SRL), particularly in the aspects of learning planning, motivation, behavior, metacognition, and learning evaluation, had not been optimal. This study aimed to determine the effectiveness of Problem Based Learning (PBL)-based Student Activity Sheets (LKPD) on the self-regulated learning of fifth-grade elementary school students. This study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The population consisted of 40 fifth-grade students, with 38 regular students selected as the sample through purposive sampling. Data were collected through observation, documentation, and SRL questionnaires. Data analysis included validity, reliability, N-Gain, normality, homogeneity, linearity, and simple linear regression tests.The results showed that the use of PBL-based LKPD was effective in improving students’ SRL. The simple linear regression test showed that the Fcount value of 42.782 was higher than the Ftable value of 4.45, with a significance value lower than 0.05. Therefore, the use of PBL-based LKPD had a significant effect on the self-regulated learning of fifth-grade elementary school students.